1998
DOI: 10.1007/bf02484612
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl-Tn antigen as a useful predictor of poor prognosis in patients with advanced stomach cancer

Abstract: Sialyl-Tn antigen (STn) expression was studied immunohistochemically in 211 primary advanced gastric carcinomas. The overall rate of positive STn staining was 17% (35/211), and positive STn staining was found not to be correlated with tumor size, depth of invasion, lymph node metastasis, liver metastasis, or peritoneal metastasis. However, patients with tumors that were immunoreactive for STn demonstrated significantly lower survival (P < 0.05). Multivariate analysis revealed that STn staining was an independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Inversely, a tendency towards increased STn expression frequency in poorly differentiated cells was observed in liver and bladder cancers [29]. Finally, the histological grade does not seem to affect STn expression in gastric [25,64,65] or breast cancer [66,67]. All these observations are subjected to differences in histological grading of each tumor type, which may reflect different biological events for the cancer cells, depending on the organ considered.…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Inversely, a tendency towards increased STn expression frequency in poorly differentiated cells was observed in liver and bladder cancers [29]. Finally, the histological grade does not seem to affect STn expression in gastric [25,64,65] or breast cancer [66,67]. All these observations are subjected to differences in histological grading of each tumor type, which may reflect different biological events for the cancer cells, depending on the organ considered.…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
“…For a majority of the authors, STn expression detected in tissue and/or sera samples of patients with gastric cancers was correlated with depth of invasion [25,42,72,73,74,75,76], lymph vessel and venous invasion [65,72,73] and peritoneal dissemination [25,73]. Ikeda et al .…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Recent studies using monoclonal antibodies (mAbs) have demonstrated an intimate relationship between the aggressive growth of gastric cancer and expression of carbohydrate epitopes, such as sialyl Tn (STn) and sialyl-Lewis a (SLe a ) antigens. [6][7][8][9][10][11][12][13] On the other hand, there is little information about lectin-binding carbohydrates, [14][15][16] even though dynamic changes in carbohydrate expression on epithelial cells of the gastric wall have been demonstrated by lectin histochemistry. [17][18][19][20][21] Furthermore, none of the studies using mAbs have focused on early gastric cancer.…”
Section: Introductionmentioning
confidence: 99%